Barriers and leverage points for seeing alcohol differently in integrated care systems in England: a senior stakeholder interview study - Jim McCambridge; Duncan Stewart; Mary Madden (BMJ Publishing Group, 2024)
Introduction Integrated care systems (ICSs) are the latest major innovation aiming to develop localised, integrated health and social care services to improve population health in England. Nationally, alcohol has received limited attention in National Health Service (NHS) strategic decision-making relative to its burden of harm, which varies considerably in localities. We examined decision-making and progress on alcohol in two contrasting ICSs, identifying systemic barriers to dealing with alcohol harm and potential leverage points, particularly in primary care.Methods Qualitative case study in two ICSs differing in strategic prioritisation of alcohol in Northern England. In-depth semistructured interviews with 14 senior stakeholders followed by constructionist thematic analysis.Results ICS formation occurred when services had been under sustained pressures with lines of communication and accountability emergent and unclear. Stakeholders identified fundamental disconnects between prevention and treatment. ICS strategic prioritisation of alcohol engendered new perspectives and novel actions. Even where not prioritised, there was a demand for placing alcohol work within a population frame. Attention to alcohol was somewhat precarious in primary care and overlooked in NHS health inequalities discourse. Reframing alcohol clinically as a drug was seen as having unrealised potential to prevent or delay disease onset and complications and improve NHS effectiveness. While congruent with the vision of how the new system should be working, there were doubts about capacity in current circumstances.Conclusions There is much to do to create a joined-up, system-wide approach to alcohol, and thus a strong case for a national NHS alcohol strategy to guide ICS decision-making, addressing links between NHS work and public health.